Clinico - Epidemiological Profile of Diabetic Ketoacidosis in Hospitalised Children at a Tertiary Health Care Centre - Mali, Vijay Tukaram; Kavthekar, Saiprasad Onkareshwar; Verma, Sachin; Kurane, Anil Bapurao; Patil, Nivedita Balasaheb; Kulkarni, Suhas Panditrao (Journal of Nepal Paediatric Society, 2021)
Introduction: Diabetic Ketoacidosis (DKA) presents with spectrum of clinical manifestations and awareness regarding this amongst physicians is crucial. The study aimed to chronicle the clinical profile of DKA in type 1 diabetes mellitus (T1DM) children. Methods: The study was conducted at a tertiary care hospital including patients with signs and symptoms of DKA with either debut or established T1DM (n = 38). Detailed clinical history, examination and laboratory investigations were carried out. Differences in frequency distribution concerning demographics and clinical data were analysed in R-studio software (v.1.2.5001). Results: Kussmaul breathing (49.97%) was the commonest presentation. Infection (39.46%) and poor compliance due to inadvertent omission of insulin therapy (50%) were the commonest precipitating factors. Mild, moderate and severe dehydration was present in 44.74%, 39.47% and 15.79% respectively. Forty-five percent patients had moderate while 34.21% and 21.05% had mild and severe DKA respectively. Seventy-five percent and 52% patients were below 3rd percentile for height and weight respectively. High number of patients had past history of viral infections, were diagnosed in winter, belonged to 2nd or 3rd birth order and from lower middle class. Patients with poor compliance to insulin belonged to lower middle (40%), upper lower (53.33%) and lower class (6.67%). Conclusions: DKA can be diagnosed early by identifying dehydration, Kussmaul breathing, polyuria and altered sensorium. Infection and poor compliance due to omission of insulin therapy were the commonest and preventable precipitating factor for DKA. Poor compliance to insulin can be attributed to lower socioeconomic class. Awareness among physicians concerning clinical profile of DKA is crucial.